Pengaruh Penggunaan Webform Terhadap Efektivitas Layanan Customer Service Bank BSI KC Jember Sudirman - Nanda Alfiani; Nadia Andini; Ana Pratiwi (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2026)
The rapid development of digital technology has encouraged banking institutions to continuously innovate in improving the quality of customer services. One of these innovations is the use of webforms as a digital service medium that facilitates administrative processes and communication between customers and customer service officers, making them faster, more practical, and more efficient. This study aims to determine the effect of webform utilization on the effectiveness of customer service performance.This study employed a quantitative approach with a descriptive research design. The population consisted of all customer service officers who use webforms in serving customers at Bank Syariah Indonesia (BSI) KC Sudirman Jember. The sample was selected using a purposive sampling technique, focusing on customer service officers who actively utilize webforms in their daily operational activities. Data were collected through observation, documentation, and literature review. The data sources comprised primary data obtained from observations of customer service activities and secondary data derived from company documents, internal reports, and relevant literature. Data analysis was conducted using descriptive quantitative methods by comparing service conditions before and after the implementation of webforms. The results indicate that the use of webforms at Bank Syariah Indonesia KC Sudirman Jember significantly assists customer service officers in providing services to customers. The implementation of webforms accelerates data entry processes, improves service efficiency, and reduces customer waiting times. However, webforms still have limitations because certain services require customers to visit the bank directly for verification and transaction processes, making the system less practical in some cases.